2017
DOI: 10.3389/fnins.2017.00365
|View full text |Cite
|
Sign up to set email alerts
|

Brain Responses to a 6-Hz Binaural Beat: Effects on General Theta Rhythm and Frontal Midline Theta Activity

Abstract: A binaural beat is a beat phenomenon that is generated by the dichotic presentation of two almost equivalent pure tones but with slightly different frequencies. The brain responses to binaural beats remain controversial; therefore, the aim of this study was to investigate theta activity responses to a binaural beat by controlling factors affecting localization, including beat frequency, carrier tone frequency, exposure duration, and recording procedure. Exposure to a 6-Hz binaural beat on a 250 Hz carrier tone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 31 publications
3
74
0
Order By: Relevance
“…Monaural beats elicit higher cortical entrainment at the beat frequency than their binaural counterparts Both beat types entrained the brain at their beat frequencies, with monaural conditions eliciting the highest response when compared to binaural conditions. In terms of Theta beat frequency, both Jirakittayakorn & Wongsawat (2017) and Karino et al (2006), found similar entrainment using Theta binaural beats with exposure times between five and ten minutes. Following Garcia-Argibay's conclusions (2018), relatively long exposure time and non-masked binaural beats (i.e.…”
Section: Binaural and Monaural Beats Elicit Subcortical Responses At mentioning
confidence: 73%
See 1 more Smart Citation
“…Monaural beats elicit higher cortical entrainment at the beat frequency than their binaural counterparts Both beat types entrained the brain at their beat frequencies, with monaural conditions eliciting the highest response when compared to binaural conditions. In terms of Theta beat frequency, both Jirakittayakorn & Wongsawat (2017) and Karino et al (2006), found similar entrainment using Theta binaural beats with exposure times between five and ten minutes. Following Garcia-Argibay's conclusions (2018), relatively long exposure time and non-masked binaural beats (i.e.…”
Section: Binaural and Monaural Beats Elicit Subcortical Responses At mentioning
confidence: 73%
“…Auditory stimulation at the theta frequency band (4 -7 Hz) has been associated with positive emotional experiences and introspection (Aftanas & Golocheikine, 2001), reduced perceived pain in patients with chronic pain (Zampi, 2015), states of meditation and decreased alertness (Jirakittayakorn & Wongsawat, 2017) and enhancement of immediate verbal memory (Ortiz et al, 2008). Furthermore, theta cortical activity is related to concentration, focused attention and a general meditative state (Takahashi et al, 2005;Lagopoulos et al, 2009).…”
Section: Frequency Choice: Thetamentioning
confidence: 99%
“…Auditory stimulation at the u frequency band (4-7 Hz) has been associated with positive emotional experiences and introspection (Aftanas and Golocheikine, 2001), reduced perceived pain in patients with chronic pain (Zampi, 2015), states of meditation and decreased alertness (Jirakittayakorn and Wongsawat, 2017), and enhancement of immediate verbal memory (Ortiz et al, 2008). Furthermore, u cortical activity is related to concentration, focused attention and a general meditative state (Takahashi et al, 2005;Lagopoulos et al, 2009).…”
Section: Frequency Choice: Hmentioning
confidence: 99%
“…The dichotic presentation of two nearly equivalent pure tones with slightly different frequencies lead to what we called 'beat' in the brain. The beat in this case generated within the brain and is referred to as a 'binaural beat' (Jirakittayakorn and Wongsawat, 2017;Chaieb et al, 2015). When a tone of 410 Hz presented to the right ear as an example and a 420 Hz one to the left, then a beat of 10 Hz shall be perceived and located in the brain with carrier frequency of 415 Hz (Chaieb et al, 2015;Anonymous, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The researchers by Padmanabhan et al (2005) found that binaural beat audio has the role in decreasing acute pre-operative anxiety affectively. For inducing a meditative state, Jirakittayakorn and Wongsawat (2017) suggested that 6 Hz binaural beat on a 250 Hz carrier tone can be regard as a good stimulus. Mihajloski et al (2014) developed a new procedure of evoking transient auditory evoked potentials to binaural beats by adopting frequency modulated stimuli.…”
Section: Introductionmentioning
confidence: 99%